Exposition Of Nehemiah's Leadership Model: A Spiritual and Transformational Leadership Approach - Asnita Basir Leman (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
Many world leadership motivators use the Bible's principles and apply them in the secular area, and they are very successful. Ironically, when Christians want to emulate that success and reuse those principles in spiritual leadership of the church, it turns out that in the process of 're-use' and 're-pack' someone has been eliminated, Christ is no longer be the center of that leadership. This article aims to present an exposition of Nehemiah's leadership model, conduct a comparative analysis based on spiritual leadership and transformational leadership theory, then synthesize according to theological context and its current application concepts based on the worldview Christian. The results of the research are expected to be an inspiration for the Christian leadership holistically.